Kawasan problematik pendidikan Islam - Alfiatin, Lisa Nur Alif (Maliki Interdisciplinary Journal, 2024)
Human knowledge can progress from the lowest level to the highest. Education has the ability to propel the existing education system in Indonesia to the forefront and produce competent, talented, and morally upright students. Education is invaluable and indispensable in daily life. Considering the significance of education, the government must be prepared to address the challenges and provide solutions that educational institutions in Indonesia will face. These challenges will always necessitate the involvement of the government. There are numerous issues affecting educational institutions in Indonesia, which can disrupt their functioning. Examples include inadequate infrastructure, declining teacher quality, and the need to instill moral values in adolescents. Educational institutions have been proactive in devising the best solutions to tackle these problems. In summary, the importance of education in acquiring knowledge and shaping competent and morally upright individuals. The government must actively address the various challenges faced by educational institutions, such as inadequate infrastructure, declining teacher quality, and the need to instill moral values. By doing so, the education system in Indonesia can thrive and produce well-rounded individuals capable of discerning between right and wrong, avoiding negative influences.